Cutting down: insights from qualitative studies of smoking in pregnancy. (13th November 2013) - Graham, Hilary; Flemming, Kate; Fox, David; Heirs, Morag; Sowden, Amanda
Abstract The adverse effects of smoking in pregnancy are minimised if the mother quits completely in early pregnancy. Smokers are therefore advised to quit abruptly; cutting down is not recommended either as a method of, or alternative to, quitting. However, most pregnant smokers do not quit and cutting down is widely reported. Evidence comes primarily from quantitative studies; qualitative research has contributed little to understandings of cigarette consumption in pregnancy. In consequence, little is known about the place and meaning of cutting down for pregnant smokers. The paper investigates this important dimension of maternal smoking. It explores perceptions and experiences of cutting down among pregnant smokers by examining data from a systematic review of qualitative studies of smoking in pregnancy. The studies were located in high‐income countries and published between 1970 and 2012. Twenty‐six studies, reported in 29 papers, were included, representing over 640 women. Meta‐ethnography guided the analysis and synthesis. Data (participants' accounts and authors' interpretations) were extracted and coded; codes were progressively combined to identify overarching themes ('lines of argument'). Running through the lines of argument was evidence on cutting down; the paper presents and analyses this evidence. The analysis indicates that cutting down figured centrally as both a method of quitting and, for persistent smokers, a method of harm reduction. While pregnant women were aware that official advice was to quit abruptly, cutting down was seen as a positive behaviour change in often‐difficult domestic circumstances, and one that health professionals condoned. Our findings suggest that cutting down in pregnancy, as an aid and an alternative to quitting, requires greater recognition if healthcare and tobacco control policies are to be sensitive to the perspectives and circumstances of pregnant smokers.